Morphofunctional Characteristic of Edema-Swelling of the Cerebral Cortex of White Rats After Severe Traumatic Brain Injury Without the Use of L-Lysine Escinate and Against the Background of Its Use - I. P. Koshman; S. S. Stepanov; A. Y. Shoronova; A. G. Kalinichev; V. A. Akulinin; D. B. Avdeyev; V. I. Sergeyev (Неотложная медицинская помощь, 2020)
Aim of study The study is devoted to a morphometric assessment of the manifestations of edema-swelling of the somatosensory cortex (SSC) of the brain of white rats after severe traumatic brain injury (TBI) without using L-lysine escinate and when using it as a therapeutic effect.Material and methods We stained sections with hematoxylin-eosin and performed morphometric methods. On thin (4 μm) serial frontal sections of SSC, neurons and microvessels in the control (intact animals, n=5) were examined in 1 (n= 5), 3 (n=5), 5 (n=5), 7 (n=5) and 14 (n=5) days after injury without treatment (n=25, comparison group) and with treatment (n=25, main group). In color raster images (lens x100), using the plug-in filter “Find Maxima”, maximum brightness areas (MBA) were determined , which were then analyzed using the “Analyze Particles” program from ImageJ 1.52 s. MBA corresponded to SSC sites with a high degree of hydration of nerve tissue - edema-swelling. Statistical hypotheses were tested using nonparametric criteria.Results and discussion In control animals, a low degree of hydration of SSC tissue was noted (relative area 3-8%). In the comparison group, 1 and 3 days after STBI, foci of edema-swelling covered up to 30% of SSC, in 5 days - up to 15%, in 7 days - up to 20%, in 15 - up to 18%. Significant heteromorphism and heterogeneity of changes in the neuropil around neurons and blood vessels was noted. In the dynamics of the post-traumatic period, the proportion of large foci of edema-swelling (intra- and perineuronal, perivascular) decreased. In the main group, one day after STBI, there was a statistically significantly smaller number of foci of edema-swelling and their total relative area. The values range of these variables significantly decreased. L-lysine escinat affected the water balance most effectively in the acute post-traumatic period (day 1 and 3). The drug “smoothed out” the manifestation peaks (number, focal area) of edema-swelling: the values of the studied morphometric indicators were statistically significantly different. Consequently, morphometric signs of hydropic dystrophy after STBI were detected in both studied groups during the 15 days of observation.Conclusion The degree of SSC nervous tissue hydration increased after STBI. L-lysine escinate statistically significantly reduced manifestations of hydropic dystrophy. The drug significantly affected the degree of hydration of neural tissue observed in the early post-traumatic period.